High corrosion resistance and weak corrosion anisotropy of an as-rolled Mg-3Al-1Zn (in wt.%) alloy with strong crystallographic texture. Issue 1 (December 2017) - Wang, B.; Xu, D.; Xin, Y.; Sheng, L.; Han, E.
Abstract Combining with electrochemical corrosion measurements, immersion and hydrogen evolution testing performed in 0.9 wt.% NaCl solution at 37 °C, the corrosion resistance of an as-rolled Mg-3%Al-1%Zn alloy before and after a 3% compressive strain along the rolling direction was investigated. Results revealed that the corrosion behavior of differently oriented surfaces of the as-rolled samples with a strong basal texture was obviously different. Among them, the corrosion rate of sample surface with the orientation parallel to the normal direction (ND) of the plate was the fastest, the corrosion rate of sample surface with the orientation parallel to the rolling direction (RD) of the plate took the second place and the corrosion rate of sample surface with the orientation parallel to the transverse direction (TD) was the slowest. After being pre-strained, the activation of a high density of 10–12 twins could remarkably reduce the corrosion rate of surrounding α-Mg matrix and simultaneously weaken the corrosion anisotropy between differently oriented samples. The main reason was that similar to grain boundaries, twin boundaries acted as physical barriers to the corrosion attack. Moreover, the activated twins increased the protectiveness of surface films and then suppressed the micro corrosion couples occurred in twinned grains.